Implementation of Levels of Thinking Skills and Communicative Language Ability in English National Exam - Hervina Hervina; Rendi Afriadi (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to explore the implementation of the learning domain, which is manifested in the level of thinking skills, namely HOTS and LOTS, and the concept of CLA in the English national exam. The research method used is the descriptive analysis by analyzing all the questions in the English national exam for SMK in 2014/2015. The results showed that all the questions in the English national exam for SMK 2014/2015 are directed to assess students' cognitive skill domains with different skill levels and thinking processes. The concept of HOTS, LOTS and CLA have been implemented and applied in the construction and design of this exam. In conclusion, the implementation of English national exam has implemented requirement of good language testing. Keywords: Communicative Language Ability, National Exam, Standardized Test, Thinking Skills